2020
DOI: 10.1590/1806-9061-2019-1158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fat Sources and Emulsifier Levels in Broiler Diets on Performance, Nutrient Digestibility, and Carcass Parameters

Abstract: The objective of the current study was to check the effect of fat types and polyglycerol polyricinoleate (PGPR) levels in broiler diets on broilers performance. For this purpose, three sources of fat {soy oil (SO), poultry oil (PO), and oxidized oil (OO) (oxidized soy oil)} and four levels of PGPR were used in a 3×4 factorial arrangement. The trial had 12 different dietary treatments: (T1) basal ration (BR) containing SO without PGPR supplementation, (T2) BR containing PO without PGPR supplementation, (T3) BR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(67 reference statements)
1
6
0
1
Order By: Relevance
“…In contrast to this study, Fonseca et al (10) used a soy lecithin emulsifier and obtained a better yield of prime cuts compared to the control treatment. However, similar to the present research, Kamran et al (11) studied emulsifier levels in different lipid sources in the diet of broilers and observed no influence on carcass yield despite the obtained differences in productive performance.…”
Section: Carcass Yieldsupporting
confidence: 87%
“…In contrast to this study, Fonseca et al (10) used a soy lecithin emulsifier and obtained a better yield of prime cuts compared to the control treatment. However, similar to the present research, Kamran et al (11) studied emulsifier levels in different lipid sources in the diet of broilers and observed no influence on carcass yield despite the obtained differences in productive performance.…”
Section: Carcass Yieldsupporting
confidence: 87%
“…Emulsifier-like feed additives have been widely used in terrestrial animals [1][2][3][4][5][6]. In recent years, they are also being more and more frequently used in farmed fish, typically bile acids [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Emulsifier (0.035%) in broilers fed diet containing different oil levels (1, 2 and 3%) had greater heart weight (8.51 vs 7.01 g) than control group (Abbas et al, 2016). Kamran et al (2020) used different levels (0, 0.025, 0.035, 0.045%) of PGPR in broilers diet reared on three oil sources (poultry fat, soy oil and oxidized soy oil) and reported that lightness, redness, yellowness and pH were not influenced by different dietary treatments. Broilers diet supplemented with multi-enzyme and emulsifier along with low density diet had no effect on breast yield with high density diet (Cho et al, 2012).…”
Section: Effect Of Emulsifier On Carcass Response and Meat Quality In...mentioning
confidence: 96%
“…Addition of 0.1% emulsifier in broilers diet had increased weight gain and FCR during the period of 0 to 19 days (An et al, 2020). Kamran et al (2020) used different levels (0, 0.025, 0.035, 0.045%) of polyglycerol polyricinoleate (PGPR) in broilers diet on three oil sources (poultry fat, soy oil and oxidized soy oil) and concluded that use of PGPR in soy oil based diet had improved FCR than control diet in broilers. Use of 0.05% lysophospholipid in broilers diet had improved feed intake and FCR (Chen et al, 2019).…”
Section: Lecithin and Lysolecithin As Emulsifiersmentioning
confidence: 99%